2021
DOI: 10.1002/acr2.11186
|View full text |Cite
|
Sign up to set email alerts
|

Takayasu Arteritis: a Systematic Review and Meta‐Analysis of Test Accuracy and Benefits and Harms of Common Treatments

Abstract: Objective Takayasu’s arteritis (TAK) is a granulomatous large‐vessel vasculitis primarily affecting the aorta and its proximal branches. TAK can be a difficult disease to diagnose and manage given the rarity of the disease as well as current limitations in biomarkers, imperfect imaging modalities, and few randomized controlled trials. Methods In developing the American College of Rheumatology/Vasculitis Foundation guideline for the management of TAK, we performed an extensive systematic literature review to gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
0
11
0
8
Order By: Relevance
“…This result indicates that stent implantation in large artery vessels is effective. Pharmacologic treatment for TA includes antithrombotic therapies, glucocorticoids, and immunosuppressive agents [ 35 , 36 ]. Methotrexate is recommended to use for the treatment of all patients with TA [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that stent implantation in large artery vessels is effective. Pharmacologic treatment for TA includes antithrombotic therapies, glucocorticoids, and immunosuppressive agents [ 35 , 36 ]. Methotrexate is recommended to use for the treatment of all patients with TA [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, imaging findings are not included as a scoring item in the ITAS (13). As patients with active TAK commonly have non-specific disease manifestations and unreliable laboratory parameters, imaging findings are of importance in monitoring disease activity in patients with TAK (19,20). On this basis, it is reasonable to combine clinical manifestations and acute phase reactants with imaging findings to yield a highly accurate disease activity assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…4a). Park et al reported a decrease in median (interquartile range) of PET Vascular Activity Score from 12 (11-15.5) to 11 (8)(9)(10)(11)(12) with infliximab therapy over a follow-up period of 30 weeks [74]. Normalization of inflammatory markers was seen in 80% (95% CI 56-98%, 2 studies, 17 patients, I 2 not assessable, Fig.…”
Section: Tnf Inhibitorsmentioning
confidence: 99%
“…While the role of DMARD therapy in ameliorating disease activity in TAK has been the subject of previous systematic reviews [6][7][8][9], there remains a need to update this information in the context of emerging new literature regarding the pharmacotherapy of TAK. Lack of extensive database searches is another limitation of existing systematic reviews on this topic [10]. In this context, we undertook a systematic review to critically evaluate the literature supporting the use of DMARDs in the management of TAK with respect to outcomes assessed by clinical assessment, angiography and other imaging modalities, inflammatory markers and relapses.…”
Section: Introductionmentioning
confidence: 99%